2019
DOI: 10.1097/sla.0000000000003225
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Treatment and Appendectomy for Uncomplicated Acute Appendicitis in Adults and Children

Abstract: Objective: The aim of this meta-analysis was to summarize the current available evidence on nonoperative management (NOM) with antibiotics for uncomplicated appendicitis, both in adults and children. Summary Background Data: Although earlier meta-analyses demonstrated that NOM with antibiotics may be an acceptable treatment strategy for patients with uncomplicated appendicitis, evidence is limited by conflicting results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
169
1
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(194 citation statements)
references
References 47 publications
10
169
1
14
Order By: Relevance
“…Previous studies demonstrated that appendicitis in elderly are associated with higher risk of perforation and complications due to more comorbidities and more challenge of accurate diagnosis [4,5]. Therefore, precise diagnosis coupled with appropriate procedure are crucial for treating appendicitis in elderly population [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that appendicitis in elderly are associated with higher risk of perforation and complications due to more comorbidities and more challenge of accurate diagnosis [4,5]. Therefore, precise diagnosis coupled with appropriate procedure are crucial for treating appendicitis in elderly population [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that laparoscopic appendectomy appears to be a method of choice in most patients presenting with the symptoms of AA [6,16]. However, recent studies such as the APPAC randomized clinical trial published by Salminen et al [20] and a meta-analysis by Podda et al [16], which included more than 3500 patients with suspicion of AA, have shown that antibiotic therapy for image-proven uncomplicated appendicitis is a viable Ovarian cyst rupture 3…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have attempted to evaluate the usefulness of hyperbilirubinemia in distinguishing AA from other conditions presenting with similar clinical symptoms, and the outcomes confirmed the hypothesis [2,15]. Moreover, in the face of growing evidence for non-surgical treatment of uncomplicated AA the search for a clinically useful marker to establish the severity of AA seems obligatory [16].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…For uncomplicated appendicitis, recent meta-analyses 4 have reported that antibiotic therapy could represent a feasible treatment option. Although the success rates of complication-free treatment generally are higher than those with surgical treatment, some studies have suggested that non-operative management for uncomplicated appendicitis does not statistically increase the perforation rates in adults and in pediatric patients receiving antibiotic treatment 5,6 .…”
Section: Introductionmentioning
confidence: 99%